CONFORMITY ASSESSMENT OF PERSONAL AND GROUP ORGANIZATIONAL CULTURE PARAMETERS OF EMPLOYEES IN THE LABOUR PROCESS - V. Ya. Ivanova (Вестник университета)
An important component of the labour process is the organizational environment that determines the conditions of interaction between workers within the framework of joint activities. Each organization has a unique organizational environment that is described in scientific theory and practice by a term called organizational culture. The author carries out the analysis of methods for measuring organizational culture, and chooses an easy-to-interpret and use diagnostic tool that clearly describes the system of organizational values of employees. The paper proposes quantitative characteristics and methods of their calculation, which allow you to compare personal and group  parameters of organizational values. The study develops a sequence of actions that describes the procedure for identifying the measure of correspondence between individual and group parameters of organizational culture. The results presented in the article are part of the study of increasing the efficiency of the labour process based on the perfection of the internal environment. The author ascertained that the contradictions existing in the system of competing values lead to a violation of the interaction between employees in the process of labour activity. The data obtained form the basis for the development of a set of measures to increase labour productivity.